Cardiac and respiratory failure in limb-girdle muscular dystrophy 2I. - Poppe, M; Bourke, J; Eagle, M; Frosk, P; Wrogemann, K; Greenberg, C; Muntoni, F; Voit, T; Straub, V; Hilton-Jones, D; Shirodaria, C; Bushby, K (2004)
Mutations in the gene encoding fukutin-related protein cause limb-girdle muscular dystrophy 2I. In this multicenter retrospective analysis of 38 patients, 55.3% had cardiac abnormalities, of which 24% had developed cardiac failure. Heterozygotes for the common C826A mutation developed cardiac involvement earlier than homozygotes. All patients initially improved while receiving standard therapy. Independent of cardiac status, forced vital capacity was below 75% in 44.4% of the patients. There was no absolute correlation between skeletal muscle weakness and cardiomyopathy or respiratory insufficiency. These complications are a primary part of this specific type of limb-girdle muscular dystrophy, with important implications for management.